Antibiotic pollution promotes dominance by harmful cyanobacteria: A case study examining norfloxacin exposure in competition experiments. Issue 2 (8th March 2021) - Li, Jing‐Jing; Chao, Jing‐Jing; McKay, Robert Michael Lee; Xu, Run‐Bing; Wang, Tao; Xu, Jun; Zhang, Jin‐Long; Chang, Xue‐Xiu
Abstract : Cyanobacterial harmful algal blooms (cyanoHABs) in freshwater lakes across the globe are often combined with other stressors. Pharmaceutical pollution, especially antibiotics in water bodies, poses a potential hazard in aquatic ecosystems. However, how antibiotics influence the risk of cyanoHABs remains unclear. Here, we investigated the effects of norfloxacin (NOR), one of the most widely used antibiotics globally, to a bloom‐forming cyanobacterium ( Microcystis aeruginosa ) and a common green alga ( Scenedesmus quadricauda ), under both mono‐ and coculture conditions. Taxon‐specific responses to NOR were evaluated in monoculture. In addition, the growth rate and change in ratio of cyanobacteria to green algae when cocultured with exposure to NOR were determined. In monocultures of Microcystis, exposure to low concentrations of NOR resulted in decreases in biomass, chlorophyll a and soluble protein content, while superoxide anion content and superoxide dismutase activity increased. However, NOR at high concentration only slightly affected Scenedesmus . During the co‐culture trials of Microcystis and Scenedesmus, the 5 μg · L −1 NOR treatment increased the ratio of Microcystis to co‐cultured Scenedesmus by 47.2%. Meanwhile, although Scenedesmus growth was enhanced by 4.2% under NOR treatment in monoculture, it was conversely inhibited by 63.4% and 38.2% when co‐cultured with Microcystis with and without NOR, respectively. Our results indicate that antibiotic pollution has a potential risk to enhance the perniciousness of cyanoHABs by disturbing interspecific interaction between cyanobacteria and green algae. These results reinforce the need for scientists and managers to consider the influence of xenobiotics in shaping the outcome of interactions among multiple species in aquatic ecosystems.